7(m-16)-3(7m-35)=21

Simple and best practice solution for 7(m-16)-3(7m-35)=21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(m-16)-3(7m-35)=21 equation:


Simplifying
7(m + -16) + -3(7m + -35) = 21

Reorder the terms:
7(-16 + m) + -3(7m + -35) = 21
(-16 * 7 + m * 7) + -3(7m + -35) = 21
(-112 + 7m) + -3(7m + -35) = 21

Reorder the terms:
-112 + 7m + -3(-35 + 7m) = 21
-112 + 7m + (-35 * -3 + 7m * -3) = 21
-112 + 7m + (105 + -21m) = 21

Reorder the terms:
-112 + 105 + 7m + -21m = 21

Combine like terms: -112 + 105 = -7
-7 + 7m + -21m = 21

Combine like terms: 7m + -21m = -14m
-7 + -14m = 21

Solving
-7 + -14m = 21

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -14m = 21 + 7

Combine like terms: -7 + 7 = 0
0 + -14m = 21 + 7
-14m = 21 + 7

Combine like terms: 21 + 7 = 28
-14m = 28

Divide each side by '-14'.
m = -2

Simplifying
m = -2

See similar equations:

| -14t+17t=-6 | | 5i+6x=(10y)i+2 | | y=-10(1)+2 | | m-23=1 | | 2g-2g+2g=20 | | 6.2h=-80.6 | | -6w+24+8w=2w+18 | | 4(y-18)=4 | | 36+3y=-3y | | p-.06p=1908 | | 209=-19(y-995) | | -20t+19t+8=19 | | -5(3r+2)=-4(2+4r) | | 990=8lw | | 10q+4q-13q+3=16 | | 0.32+1.2=2.12 | | -30(k-950)+437=-283 | | 8t=9t+7 | | 34X-21=45X+12 | | 8b+6=-6+10b | | 18=3(m-10) | | 40=4x*2 | | -24+3x=-3(-3x+4) | | 10*-5+2=y | | z+8= | | 1y+23=2Y+12 | | -6c+9=-7c | | z+13= | | -9=2-s | | 9p^5q+6p^4q^2-15p^2q^4= | | 3r+r-3=17 | | -2=9-9 |

Equations solver categories